Case study of performance assessment of overlapping shield tunnels with a small curve radius - Xu Zhang; Bin Luo; Youjun Xu; Chenxu Zhao; Huachuan Wang (Deep Underground Science and Engineering)
Abstract Due to the network planning of subways and their surrounding structures, increasingly more overlapping shields with a small curve radius have been constructed. A newly constructed upper tunnel partly overlaps a lower one, leading to the extremely complex uplift of the lower tunnel caused by the construction of a new tunnel. Based on the shield‐driven project that runs from the Qinghe Xiaoyingqiao Station to the Qinghe Station in Beijing, which adopts the reinforcement measures of interlayer soil grouting and steel supports on site, in this study, the uplift pattern of the lower tunnel and the stress characteristics of steel supports were investigated through numerical simulations and on‐site monitoring. The study results show that among all tunnel segments, the first segment of the shield witnesses a maximum uplift displacement that increases with the horizontal space between tunnels. On using either interlayer soil grouting or steel‐ring bracing reinforcement, the uplift of the tunnel lining exceeds the control value; by contrast, when these two measures are jointly applied, the uplift of the tunnel lining does not exceed a maximum value of 4.87 mm, which can satisfy the requirements of deformation control. Under these two joint measures, the soil strength between two stacked shield tunnels can be enhanced and the uplift deformation can be restricted with the interlayer soil grouting. Also, the segmental deformation and overall stability of the existing tunnel can be controlled with the temporary steel supports. The deformation of circumferential supports and segments is closely related to each other, and the segmental uplift is controlled by H‐shaped steel supports. With the increase in the horizontal space between twin shields, the effect of the construction would gradually weaken, accompanied by a gradual reduction of the stresses of steel supports. These findings provide a valuable reference for the engineering design and safe construction of overlapping shield tunnels with a small curve radius.